Analysis of individual block length of amphiphilic di- & tri-block copolymers containing poly(ethylene oxide) and poly(methyl methacrylate). Issue 66 (29th August 2017) - Tufail, Muhammad Khurram; Abdul-Karim, Rubina; Rahim, Sana; Musharraf, Syed Ghulam; Malik, Muhammad Imran
Abstract : Estimation of individual block lengths and extent of homopolymers. Abstract : In this study, di- and tri-block copolymers composed of PEO and PMMA are synthesized and comprehensively characterized. Block copolymers are synthesized by ATRP of MMA using bromine-terminated PEO macro-initiators of varying molar masses ranging from 2000 to 20 000 g mol −1 . End-group transformation of the macro-initiator is confirmed by NMR and FTIR. Initial feed ratios of macro-initiator and monomer are varied systematically in order to have block copolymers of different total molar mass, individual block lengths and compositions. Chemical composition of the block copolymers as obtained by NMR complements the expected values based on initial macro-initiator to monomer ratios. Block copolymers are characterized by size exclusion chromatography, and liquid chromatography at critical conditions on both RP and NP columns. The most complex distribution of block copolymers was obtained at the critical adsorption point of PMMA on a RP column. Fractions were collected at critical conditions of PMMA, and were subjected to detailed analysis by SEC, LCCC–PEG, and NMR in the second dimension. Two-dimensional analysis revealed details about the products that were not accessible by independent or stand-alone analysis using the same techniques.